University students from Malaysia, Indonesia and the Philippines engaged in online forum discussions / Noor Azli Affendy Lee and Marni Jamil - Affendy Lee, Noor Azli; Jamil, Marni (Academy of Language Studies, 2022)
A total of 239 university students attended the International Youth Engagement Talk Series 2022, a virtual talk series organised by the English Language Club (ELC) of Universiti Teknologi MARA, Cawangan Pulau Pinang (UiTMCPP), in a joint collaboration with Unit Ko-Kurikulum of UiTMCPP, Universitas Muhammadiyah Pontianak (UM Pontianak) of Indonesia, and two universities from the Philippines - Mindanao State University - lligan Institute of Technology (MSU I IT) and Xavier University - Ateneo de Cagayan. Conducted live via StreamYard and broadcasted on the club’s YouTube channel, the 4-day programme from 17 May to 20 May 2022 started at 8.30 p.m. and ended at 10.30 p.m. The programme consisted of a webinar talk with professional guests and a forum discussion between delegates from several universities.